Cuento infantil - MONTES, Graciela selector (CENTRO EDITOR DE AMERICA LATINA, 1982)
Contenidos: cuentos de PERRAUT, Charter; GRIMIN, Jacob; GRIMIN, Wilhelm; ANDERSEN, Mans Cristian; BROWNING, Robert; COLLODI, Carla